Pengembangan Kawasan Minapolitan Sebagai Daya Tarik Wisata Minat Khusus di Kabupaten Serdang Begai Sumatera Utara - Mohamad Ridwan; Muhammad Ikhsan Andi (Universitas Muslim Indonesia, 2024)
The basic idea of ​​Minapolitan development is strengthening the synergy between economic growth and preserving environmental functions, as well as efforts to find environmentally friendly technology and instruments that can ensure the preservation of environmental functions to formulate appropriate strategies for developing the people's economy. Community empowerment through the development of the Minapolitan Region can include the integration of related supporting resources, including tourism. On the one hand, the Minapolitan Region is one of the regional tourism resources that is able to diversify tourism products so that it can present many choices (diversification) of tourist attractions to tourists. On the other hand, the Minapolitan area can be supported by tourism development that involves active community participation. This research is specifically aimed at assessing the potential of Minapolitan in the Nipah Beach area and its surroundings which can be developed as a tourist attraction, knowing the availability of supporting facilities for Minapolitan development in the Regency